Quality control of Semen Ziziphi Spinosae standard decoction based on determination of multi-components using TOF-MS/MS and UPLC-PDA technology - Di Wang; Qing Li; Ran Liu; Huarong Xu; Yidi Yin; Yifan Wang; Huijia Wang; Kaishun Bi (Elsevier, 2019)
A sensitive, fast and comprehensive method for the quality assessment of Semen Ziziphi Spinosae (SZS) standard decoction with characterization of its chemical components was developed and validated. UPLC-Q/TOF-MS/MS system was used to identify thirty-six chemical components of SZS standard decoction which included nucleosides, phenolic acids, alkaloids, and flavonoids. Furthermore, a UPLC-PDA method was validated to simultaneously determine adenosine, protocatechuic acid, magnoflorine, catechin, protocatechin, vicenin II, spinosin, kaempferol-3-rutinoside, and 6'''-feruloylspinosin which represent four species of characteristic compounds. The qualitative method had been validated according to Chinese Pharmacopoeia (2015 edition) in terms of lineary, repeatability, recovery and stability for all analytes, with the results showing good precision, accuracy and stability. In conclusion, the method using UPLC combined with MS and PDA provided a novel way for the standardization and identification of SZS standard decoction, and also offered a basis for qualitative analysis and quality assessment of the preparations for SZS standard decoction. Keywords: Identification, Semen Ziziphi Spinosae (SZS), Standard decoction, Quality assessment, UPLC, TOF-MS/MS